2008
DOI: 10.1007/s00198-008-0760-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimum level of jumping exercise required to maintain exercise-induced bone gains in female rats

Abstract: Eight weeks of jumping exercise-induced bone gains could be maintained for a period of 24 weeks with follow-up exercise consisting of 11% to 18% of the initial exercise load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Rats in the jumping group and combined jumping and honey supplementation group were trained to jump using a previously described protocol [21]. Jumping exercises were carried out from 8:30 a.m. to 11:30 a.m. Each rat was subjected to the exercise for 5 minutes duration per day for 5 days per week.…”
Section: Training Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Rats in the jumping group and combined jumping and honey supplementation group were trained to jump using a previously described protocol [21]. Jumping exercises were carried out from 8:30 a.m. to 11:30 a.m. Each rat was subjected to the exercise for 5 minutes duration per day for 5 days per week.…”
Section: Training Programmementioning
confidence: 99%
“…The effects of jumping on bone in these animals depend on forces generated by the hind limbs, thus the hind limb tibias were examined in this study [21]. After removal of the flesh from the tibia bones, they were wrapped in saline-soaked gauze pads to prevent dehydration and put into labeled plastic bags and stored at -80 °C (Heto Ultra Freezer 3410, Denmark) for subsequent measurements at the later date [21].…”
Section: Measurement Of Bone Mineral Density Using Peripheral Quantitmentioning
confidence: 99%
“…) unchanged, is not apparent. It might result from a high impact influencing the bony structure by redistributing the bony materials from the endosteal region toward the periosteal region . This phenomena also triggered a shift in the mass distribution with respect to the bone neutral axis, which significantly increased the polar area moment of inertia (Ip) in the HI cyclic group (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…11 The present research group has carried out a few previous studies to investigate the effects of exercise alone and also combined effects of exercise with nutritional supplementation on bone health. For instance, Ooi, et al, 12 found that bone mass and strength were significantly higher in jumping rats compared to controls. These findings imply that exercise can enhance bone mass and strength.…”
Section: Introductionmentioning
confidence: 99%